Firm characteristics and the use of investment decision techniques in the global south: Evidence from Ghana - Anthony Owusu-Ansah; Nene Lartey Addico; Godfred Amewu (Cogent Business & Management)
This study uses a survey approach to investigate how managers associated with thirty (30) firm characteristics subgroups apply thirty-seven (37) investment decision techniques in practice in a frontier market covering: capital budgeting, cost of equity, cost of capital, and adjustments for other types of systemic risk. The results show that 27 out of 30 firm subgroups significantly apply a payback period, and 0 out of 30 firm subgroups significantly apply any of the cost of equity estimation techniques investigated, deviating from the current literature. Nineteen out of 30 firm subgroups significantly apply a single common firm-wide discount rate for all projects, which is in line with global trends but inappropriate. It seems that frontier market managers are leaning toward simplicity as payback period, no cost of equity estimation and using a single common firm-wide discount rate do not properly account for time and risk. This may lead to less optimal investment decisions: resulting in firm value degradation. Promoting policies that reduce uncertainties in frontier markets may encourage the dominant use of net present value, cost of equity estimation and opportunity risk-adjusted cost of capital techniques to support firm value maximisation.